Pengaruh Budaya Organisasi terhadap Kinerja Karyawan di X Resort Bali - Tatiana, Putri Maura; Ida Ayu Kalpikawati; Sri Sulistyawati, Ni Luh Ketut (Program Studi Administrasi Perhotelan, 2024)
Organizational culture influences employees by shaping their beliefs, values, andexpectations, which in turn impacts the success of a company and the performance of itsstaff. This research aimed to assess how organizational culture affects employeeperformance at X Resort Bali. The study involved a total of 264 employees from X Resort Bali,with a sample of 72 selected using proportionate stratified random sampling. Data analysiswas conducted using simple linear regression, t-tests, and the coefficient of determination,with SPSS version 29 for Windows. The findings indicate that organizational culture has apositive and significant effect on employee performance, evidenced by a t-value of 13.174(greater than the critical value of 1.666) and a significance level of 0.001 (less than 0.05).Organizational culture was found to account for 71.3% of the variation in employeeperformance at X Resort Bali.